PENGARUH MENTAL ACCOUNTING, SISTEM INFORMASI AKUNTANSI, MODAL USAHA, DAN PEMANFAATAN E- COMMERCE TERHADAP KINERJA UMKM DI KABUPATEN MADIUN - Siti Suharni; Winda Ayu Lestari; Lely Kumalawati (JAMER : Jurnal Akuntansi Merdeka, 2025)
This research examines the influence of Mental Accounting, Accounting Information Systems, Business Capital, and E-Commerce Utilization on the Performance of MSMEs in Madiun Regency. The type of research used in this study is quantitative. This research examines the influence of Mental Accounting, Accounting Information Systems, Business Capital, and the Utilization of E-Commerce on the Performance of MSMEs in Madiun Regency. The type of research used in this study is quantitative. Data were obtained by distributing questionnaires in the form of Google Form links and barcodes to MSME actors. The population in this study consists of MSME actors registered with the Department of Trade, Cooperatives, and Micro Enterprises in Madiun Regency. The sampling technique used the method of proportionate stratified random sampling with 100 respondents. Data analysis was conducted using multiple linear regression analysis assisted by the SPSS version 27 for Windows program. The hypothesis results show that the Mental Accounting variable is 0.000, the Accounting Information System variable is 0.000, the Business Capital variable is 0.000, and the E-Commerce Utilization variable is 0.000. With these results, it can be stated that Mental Accounting, Accounting Information Systems, Business Capital, and the Utilization of E-Commerce have a significant positive effect on the Performance of MSMEs in Madiun Regency